A Methodology for Modelling of Steady State Flow in Pelton Turbine Injectors - Bajracharya, Tri Ratna; Shrestha, Rajendra; Timilsina, Ashesh Babu (Journal of the Institute of Engineering, 2019)
Pelton turbine is a high head-impulse type turbine. The high-speed jet strikes the symmetrical semi ellipsoidal buckets, thus transferring the momentum within short period of time, impulse. The conversion of potential energy of water to kinetic energy in the form of jet is done by a nozzle with internally fitted spear or needle, the assembly in known as injector. The jet quality includes but is not limited to jet velocity, velocity distribution ‘velocity profile’, core location etc. In this study, the modeling of flow in Pelton turbine injector is done by commercial Computational Fluid Dynamics (CFD) solver on a three-dimensional flow domain. The results obtained from CFD modelling are then compared against the experimental observations and previously published literatures. The jet streamline, jet velocity profile and jet core location are then studied. As observed experimentally, the mean jet diameter reduces as the nozzle opening decreases. In addition, like the experimental observations, the jet first contracts and then expands. The diameter of the contraction is then normalized with nozzle exit diameter and is plotted for both experimental observations as well as the results of the numerical simulation. The maximum error between experimental and numerical analysis of jet contraction is 20%. The jet core is located at region axially ahead of needle tip.